Production Innovation 'Jelly Siwalan Dry' for Extending the Endurance of Fruit Consumption - Kalista, Anggia; Tri Sanjaya, Krishna; Wardhono, Agus (Kontribusia : Research Dissemination for Community Development, 2021)
PRODUCTION INNOVATION 'JELLY SIWALAN DRY' FOR EXTENDING THE ENDURANCE OF FRUIT CONSUMPTION Anggia Kalista, Krishna Tri Sanjaya, Agus Wardhono. ABSTRACT Siwalan is the fruit of a palm tree which a lot of growing up in the City of Tuban. The fruit is less favored because of quick foul and difficult to eat it. The author tried to expand the innovation and introduced it to society how the way of consuming Siwalan practically, effectively, one of them is to process it into candy 'Dried Jelly Siwalan'. The purpose of this innovation is to so extend the duration of consumption of Siwalan to be able to survive more than one month at room temperature and two months in the fridge without preservatives. Dried Candy Jelly Siwalan is made from natural ingredients and interesting colors, this is intended to increase the interest of consumption of society in particular children and tourists who effect on the creation of business opportunities for the improvement of the economy of the community. Keywords:Dried Jelly Siwalan; Innovation; Siwalan